Emergence of blaNDM–1-carrying Enterobacter chengduensis in China - Fu, Hongyu; Zhu, Zhichen; Wang, Xiao; Lv, Jingnan; Zhu, Jie; Chen, Liang; Yu, Hua; Du, Hong (Frontiers in Microbiology, 2024)
Introduction Enterobacter chengduensis was defined as a novel species in the genus. Enterobacter in 2019, however, antimicrobial resistance, such as carbapenem resistance, has rarely been described in E. chengduensis. This study described the molecular features of four carbapenem-resistant E. chengduensis strains collected from a tertiary health care hospital in Southwest China. Methods Whole genome sequencing (WGS) was used to determine the genome sequence of four E. chengduensis strains. The precise species of strains were identified by average nucleotide identity (ANI) and in silico DNA-DNA hybridization (isDDH). The clonal relatedness of four E. chengduensis strains and additional 15 ones from NCBI were examined through phylogenetic analysis. The molecular features of E. chengduensis and genetic structure of carbapenemase- encoding plasmids were characterized through genomic annotation and analysis. Results The results revealed the emergence of blaNDM–1-carrying E. chengduensis strains in China. Multilocus sequence typing (MLST) analysis showed that all 19 E. chengduensis belonged to the same sequence type of ST414. Core SNP analysis suggested the potential intrahospital clonal transmission of ST414 E. chengduensis. The carbapenemase-encoding gene blaNDM–1 was harbored by an IncC-type plasmid, which was experimentally confirmed to be able to conjugate. Discussion This study reports the first emergence and potential clonal transmission of blaNDM–1-carrying E. chengduensis. Further surveillance should be advocated to monitor the dissemination of carbapenem-resistant E. chengduensis and blaNDM–1-harboring IncC-type plasmids in China.